(untitled) (International Journal of Medicine & Health Research (IJMHR) (ISSN 2395-3586), 2024)
Beta Thalassemia Major is a hereditary hemoglobinopathy that can take on different clinical expressions, with intense and multiple orofacial manifestations. It’s a major public health problem and a challenging condition that requires a multidisciplinary approach involving health practitioners from different paths (hematologist, dentist, orthodontist, cardiologist etc). The changes to the maxillofacial region stemming from this genetic form of anemia, makes it an obligation for dental practitioners to have in depth knowledge towards the nature of this disorder, its effects on oral health, and better understanding of the proper management of beta thalassemic patients. The purpose of this paper is to provide the dentist with a simplified understanding of the physiopathology of the disease, its various systemic and orofacial manifestations, and the keys to a better dental approach. Until medical research is able to provide a definitive solution to these diseases, through gene therapy or otherwise, it is necessary to welcome these patients into the cycle of dental care and offer them the most possibly complete dental experience through coordinated team work.